PENGEMBANGAN SEKTOR TRANSPORTASI UNTUK MENINGKATKAN AKSESIBILITAS KABUPATEN PULANG PISAU - Budi Sitorus; Christina N Sitorus (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
Pisau Regency is a regency division that has been 14 years separated from Kapuas, face issues such as human resources have not been adequate, the need to improve infrastructure transport sector, the availability of electricity and the availability of roads in good condition, the availability of communications networks and information, tesebut can not be materialized due to the availability of a limited budget.Data were collected through literature study, the results of research and related scientific publications. Analysis by public policy analysis in the framework of the increasing accessibility Pisau district.The purpose of research is to identify the potential Pisau Regency on demand transport sector, regional development policy analysis Pisau Regency. Benefits of the research is to provide policy advice to improve accessibility Pisau Regency.